PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X MIA SMA NEGERI 2 PEKANBARU - Pilliyah Susti Susti; Rasmiwetti '; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is about the application of active learning strategy Learning Tournamenttype that has conducted to know the increasing of student’s learning achievement on Solubility  and Constanta Solubility Product  topic in class X MIA of 2 Senior High School Pekanbaru. This research was experiment by design pretest and posttest. The sample determined randomly after doing normality and homogeneity test of 3 classes as population and then class X MIA2 as experiment group and X MIA 3 as control group. The experiment group was applied by the application of active learning strategy Learning Tournament type. The data analysis technique used was t - test. Based on the tabulation of last data obtained tcount> ttable was 1,79 ≥ 1,68 meant that the application of active learning strategy Learning Tournamenttype could increase the student’s learning achievement on Solubility  and Constanta Solubility Product topic in class X MIA of 2 Senior High School Pekanbaru. The calculation of effect size resulted on student achievement was 5,601%. Keywords : Active Learning Strategy, Learning Tournament